PROBLEMATIKA PENEGAKAN HUKUM PIDANA DAN UPAYA MENGATASINYA - Bambang Ali Kusumo (Wacana Hukum, 2010)
Abstract : The problems of criminal law enforcement lies in the function of  supervision in the management of the criminal justice system and civil law Cultur. The effort needs to be done with the oversight function of the Supreme Court beguile wider, not only include the supervision of the court process but also the supervision of the overall process of criminal law enforcement. In addition, in order to realize justice in society in the culture of civil law need to use a broad interpretation and is always carried out reform of criminal law (legalreform). Key words: oversight function, Cultur civil law